O contrato de consumo e a responsabilidade do comerciante pelo dano moral - Werner, Felipe Probst (2018)
The present study aims to investigate the differences between the types of civil liability brought by the brazilian consumer defense code and it`s relation with moral damages. To address the topic, fundamental was the analysis of consumer relations and situations of which these relations come from: juristic acts. In these first two steps of the study it was possible to realize there are great relevance in the distinction between defective goods or services and vice of the goods or service. The difference is mainly felt when observed that the obligations originating in safety (fact/defect) and adequacy (vice), because it is possible to figure out that the liability for the first ones are withdraw from de merchants. To validate the differentiation, was study the liability itself when is demonstrated differences between those contractual and non-contractual as well between subjective and objective. The liability component is essential to the final result of the study, because through it becomes possible to analyze harmful conducts, the causal link, guilt, risk, and the damage, when special attention is given to that not patrimonial (moral in a broad sense). The present study is justified because intend to demonstrate a direct way that once seen the moral damage in a costumer relation, you're facing a lack the security that might be expected of that product or service, so there is no civil liability, the priori, of the merchant. The relevance of this demonstration is legal certainty that will be generated both for the merchant as to the Judiciary as a whole. Finally, the hypothesis, that remained committed, is the withdraw of the merchant liability when established moral damage to the consumer from products or services places on the market.